2018
DOI: 10.3174/ajnr.a5741
|View full text |Cite
|
Sign up to set email alerts
|

Association between Type 1 Modic Changes and Propionibacterium Acnes Infection in the Cervical Spine: An Observational Study

Abstract: We conclude that was prevalent in the degenerated cervical spine and that type 1 Modic changes were predictive of a culture positive for. We also found that the prevalence of was not associated with previous interventions. If these results are validated by future studies, they could have a major impact on the standard of care for back and neck pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…We also see similar induction of inflammatory responses in keratinocytes by C. acnes activation of TLR signalling [ 42 , 43 ]. None of the small number of retrieved tissue samples analysed displayed any evidence of prior infection, indicating that the cells were likely C. acnes naive; the absence in 7/8 patients of type I Modic changes, which have been described as predictive of a C. acnes -positive culture [ 44 ], was also consistent with our microbiology results. Host responses to infection were variable and depended on the patient, gene target, MOI and time course.…”
Section: Discussionsupporting
confidence: 87%
“…We also see similar induction of inflammatory responses in keratinocytes by C. acnes activation of TLR signalling [ 42 , 43 ]. None of the small number of retrieved tissue samples analysed displayed any evidence of prior infection, indicating that the cells were likely C. acnes naive; the absence in 7/8 patients of type I Modic changes, which have been described as predictive of a C. acnes -positive culture [ 44 ], was also consistent with our microbiology results. Host responses to infection were variable and depended on the patient, gene target, MOI and time course.…”
Section: Discussionsupporting
confidence: 87%
“…MC1 adjacent discs have been proffered as inflammatory and most vulnerable to occult infection [14]; however, only study showed MC1 was associated with increased rates of disc bacterial growth [35]. MC specimens have been reported more infective than MC-free specimens [36][37][38][39] as have MC2 samples [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…C. acnes has been observed in IVDs with a biofilm-like morphology that precludes it presence in such samples due to surgical contamination [ 23 , 24 ]. It has also been reported that human IVDs associated with C. acnes are more likely to be characterised by type I modic changes (MC) in the endplates on magnetic resonance imaging (MRI) scans [ 25 , 26 , 27 ]. Animal studies have also shown that C. acnes infection of rabbit discs induces degeneration and inflammation of the endplate region, presenting as MCs [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%